The Alchemist in His Workshop - Bossche, Balthasar van den
This lively and richly decorated chamber presents an alchemist's workshop which is busy, productive, and filled with customers and assistants. At center, the alchemist himself--dressed in a fine satin coat with slash sleeves--sits examining a flask of urine for a young female customer and her older chaperone. A table covered with a luxurious carpet and many books sits before him, as well as a celestial globe and numerous earthenware vessels. At left and right, young assistants carry jars and tend small braziers with bellows. The shop is decorated with a paper print pinned to a beam, a taxidermied reptile specimen hung from above, and shelves of glassware. To the back of the scene, a small crowd surrounds a dentist and his patient to watch a tooth being pulled.
Keywords: Bossche, Balthasar van den, 1681-1715; Alchemists; Alchemy; Alchemy in art